Impact of degenerative spinal diseases on bone mineral density of the lumbar spine in elderly women - Muraki, Shigeyuki; Yamamoto, Seizo; Ishibashi, Hideaki; Horiuchi, Toshiyuki; Hosoi, Takayuki; Orimo, Hajime; Nakamura, Kozo (Osteoporosis international, 2004)
Degenerative diseases of lumbar spine commonly noted in elderly people may affect their lumbar spine bone mineral density (BMD). The aim of this study is to determine whether the degree of degenerative spinal diseases is correlated with lumbar spine and femoral neck BMD. This study included 630 women age 60 years or over (mean age 73.3 +/- 6.9 years) visiting the Osteoporosis Outpatient Clinic at the Tokyo Metropolitan Geriatric Medical Center. Subjects underwent anteroposterior and lateral X-rays of the lumbar spine. The score of degenerative spinal diseases for each subject was calculated according to the scores for the Kellgren-Lawrence method, osteophyte formation, bone sclerosis, disk space narrowing, and spondylolisthesis involving L1-L2 through L4-L5 interspaces. Moreover, the number of vertebral fractures at L2 through L4 was recorded. The BMD of the second to fourth lumbar spine from anteroposterior projections and femoral neck were measured using an Expert-5000 (GE Lunar, Madison, WI USA). Most subjects had degenerative diseases of the lumbar spine. Scores for the Kellgren-Lawrence method, osteophyte formation, bone sclerosis, disk space narrowing, and spondylolisthesis were positively correlated with lumbar spine BMD, while they were not correlated with femoral neck BMD. Multiple regression analysis indicated that the scores for osteophyte formation, bone sclerosis, and disk space narrowing were independently correlated with lumbar spine BMD. Thus, in this study, the scores for degenerative spinal diseases were correlated with lumbar spine BMD, while they were not correlated with femoral neck BMD. This discrepancy indicates that degenerative spinal diseases are associated with increased lumbar spine BMD measurements. Femoral neck BMD therefore may be more appropriate than lumbar spine BMD in evaluating osteoporosis in elderly women.